Comparative Market and Industry Analysis of Traditional Taxi Services and Transportation Network Vehicle Services in Metro Manila - Lee, Luis Diego D. (Philippine Management Review; Vol 25 (2018), 2019)
Amidst its highly contested entrance into the Philippine market, Transportation Network Vehicle Services (TNVS) have significantly affected the life of the typical Metro Manila commuter. This study aimed to contextualize the consumer decision process behind the selection of private land transportation options among Metro Manila users, in order to direct policy discourse for policymakers and to define the competitive dimensions in the industry for key players. In particular, the study aimed to understand the reasons behind usage and preference of traditional taxi services (TTS), Grab, and Uber – the leading private transport brands in the city. The results were intended as input into a Usage, Attitude, and Image (UAI) market research study to accurately depict consumer response to the brands. Using market reports and in-depth interviews, the study described the key service attributes that consumers consider and evaluate, compared against the core service features of these transport options. A comprehensive industry analysis was done to compare and contrast the brands objectively. The fundamental service attributes were broadly defined as ride completion, safety, value for money, convenience, and ride experience, each composed of subattributes or features that all lead to customer satisfaction. The study concludes that multiattribute variable comparison through conjoint analysis will be more suitable than a UAI study to depict consumer acceptability and preference for TNVS brands.